Detection and quantification of natural pigments extracted from callus of Echinocereus cinerascens. Issue 6 (18th October 2018) - Elias, Hashimah; Mat Taha, Rosna; Hasbullah, Nor Azlina; Othman, Rashidi; Mahmad, Noraini; Saleh, Azani; Abdullah, Sakinah
Abstract : Purpose: This paper aims to study the effect of different organic solvents on the extraction of pigments present in callus cultures of E. cinerascens . Design/methodology/approach: Attempts have been made to extract pigments from callus cultures through tissue culture system as an alternative replacement for conventional plant cultivation as tissue culture provides unlimited supplies of plant samples. Callus of E. cinerascens was induced from stem explant cultured in Murashige and Skoog medium supplemented with combination of 0.5 mg/L 6-benzylaminopurine and 0.5 mg/L α-naphthaleneacetic acid maintained under photoperiod of 16 h light and 8 h dark. Fresh samples of the callus were harvested and dissolved in various types and concentrations of solvents such as 100 per cent acetone, 80 per cent acetone, 95 per cent ethanol, 100 per cent methanol and 90 per cent methanol. Each of the mixtures was directly centrifuged to get clear supernatant containing pigments of interest. The pigments were detected and subsequently quantified via two simple techniques, ultraviolet-visible (UV-Vis) spectrophotometer and thin layer chromatography (TLC). Findings: UV-Vis spectrophotometer detected two families of pigments present in the callus cultures, namely, carotenoids (carotene and xanthophyll) and tetrapyrroles (chlorophyll a and b ). Pigment contents in various solvent extractions were estimated using spectroscopic quantification equations established. Through TLC, spots were seen on the plates, and Rf values of each spots were assessed to indicate the possible existence of carotenoids and tetrapyrroles. Originality/value: This preliminary study offers significant finding for further advance research related on natural pigments extracted from E. cinerascens that would provide profits in the future applications, especially in food industry, medicine, agriculture, etc.